The Characteristics and Determinants of Capital Structure in Shariah-compliant Firms: Empirical Evidence from Malaysia - Law, Poh Kim (2011)
This study aims to find out whether the prevailing capital structure theories (trade-off, pecking order and agency theory) are applicable on Malaysian Shariah-compliant firms. The impact of Malaysia Shariah Advisory Council (SAC)’s Shariah screening guideline and dual banking system in Malaysia on capital structure will also be examined. The empirical results show that profitability is the most dominant determinant of debt policy with significant negative relationships found with all measures of debts; Variable firm size also significant with positive relationships found for total and long-term debt while it is negatively related to short-term debt; Tangibility is found to be positively related to total debt and long-term debt but insignificant results found for short-term debt; Market-to-book ratio as proxy for growth opportunity is positively related to total debt and short-term debt but insignificant to long-term debt; In contrast, liquidity is negatively related to total debt and short-term debt but insignificant to long-term debt; Meanwhile business risk is found to be insignificant to all measures of leverage. In overall, the SAC’s Shariah screening guideline and dual banking system in Malaysia have no significant impacts on the capital structure of Malaysian Shariah-compliant firms. Hence the prevailing capital structure theories are valid in explaining the capital structure of Malaysian Shariah-compliant firms.